Implementing nanopore sequencing in a clinical laboratory: a social systems case. - Manning, Suzanne; Bloomfield, Max; Hutton, Samantha; Burton, Megan; Velasco, Charles; Tarring, Claire; White, Rhys; van der Werff, Koen (New Zealand Journal of Medical Laboratory Science, 2025)
The Molecular Pathology Department at Awanui Labs Wellington have been trialling the implementation of nanopore long-read sequencing since 2020, initially to assist the Infection Prevention and Control team. This case study explored the social systems that enabled or constrained this implementation. The study found that implementation was enabled by systems that were set up to balance the need for continued service improvement through research and innovation with the need to maintain the current level of service to clinicians and ultimately, the patients. The process also allowed oversight and coordination by management while providing a reasonable degree of autonomy for the laboratory staff to conduct the trial, including the time and flexibility required to investigate and develop the protocols. There were several implementation challenges. One challenge related to introducing a novel and unfamiliar technology while maintaining a busy routine workload, fitting in with the other work in the laboratory and securing funding. However, the main challenge specific to nanopore sequencing were the issues around accessing bioinformatics expertise, providing adequate computing power for data analysis, and the more systemic issue of data infrastructure in the health sector. The bioinformatics expertise and upgraded computer requirements have been addressed at a local level; however, the issue of national health data infrastructure and governance must be addressed if the potential of nanopore sequencing is to be realised.